The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000492648
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Shift Induced by ω -3 PUFAs and Rapamycin Lead to Cancer Cell Death

Abstract: Background/Aims: Rapamycin (Rp), the main mammalian target of rapamycin complex inhibitor, is a promising therapeutic agent for breast cancer. However, metabolic disorders and drug resistance reduce its efficacy. Epidemiological, clinical, and experimental studies have demonstrated that omega-3 polyunsaturated fatty acids (ω-3 PUFAs) significantly reduce the incidence and mortality of breast cancer and improve metabolic disorders. Methods: Three breast cancer cell lines and immunocompetent and immunodeficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 54 publications
1
38
0
1
Order By: Relevance
“…In 2018, Zhu et al reported a synergistic effect of n-3 PUFAs and rapamycin (Rp) in breast cancer cell cycle arrest, apoptosis and autophagy blockage in vitro and in vivo. They noticed that combined treatment of n-3 PUFAs and Rp significantly inhibited glycolysis and glutamine metabolism, and the antitumour effects of this combination treatment were dependent on β-oxidation and oxidative phosphorylation-mediated ROS production [242].…”
Section: Pufa-induced Ros Sensitizes Breast Cancer Cells To Chemotherapymentioning
confidence: 99%
“…In 2018, Zhu et al reported a synergistic effect of n-3 PUFAs and rapamycin (Rp) in breast cancer cell cycle arrest, apoptosis and autophagy blockage in vitro and in vivo. They noticed that combined treatment of n-3 PUFAs and Rp significantly inhibited glycolysis and glutamine metabolism, and the antitumour effects of this combination treatment were dependent on β-oxidation and oxidative phosphorylation-mediated ROS production [242].…”
Section: Pufa-induced Ros Sensitizes Breast Cancer Cells To Chemotherapymentioning
confidence: 99%
“…A new study has found that autophagy is a major way of down-regulating cell metabolism, leading to cancer cell quiescence, survival, and chemo-resistance [85, 86]. The up-regulation of autophagy mediated by metabolic dysfunction could contribute to a common mechanism of resistance to chemotherapy and radiotherapy by suppressing apoptosis, such as rapamycin (Rp) [8789]. In addition, the induction of autophagy may defend against epirubicin-mediated apoptosis, act as a pro-survival factor, and thus lead to deficient apoptosis in HepG2 and A549 cells [9092].…”
Section: Main Textmentioning
confidence: 99%
“…Previous phytochemical studies on A. ceterach , A. trichomanes and A. scolopendrium used for preparation of the extracts for the present investigation have shown that A. ceterach contains the highest levels of tannins and ω-3 polyunsaturated fatty acids (PUFAs) [ 13 ]. Both types of compounds are known for their various positive bioactivities, including anticancer effects [ 22 , 24 , 25 ]. This fact also supports the highest inhibitory effects detected for A. ceterach .…”
Section: Discussionmentioning
confidence: 99%
“…This fact also supports the highest inhibitory effects detected for A. ceterach . Recently, it has been reported that ω-3 PUFA could potentiate the anticancer activity of therapeutic agents by induction of reactive oxygen species (ROS) followed by apoptosis [ 25 ]. These findings support our data, which suggest increased ROS levels following treatment with A. cetera extracts based on the detected elevated SOD activity.…”
Section: Discussionmentioning
confidence: 99%